2022
DOI: 10.1039/d2nr02612k
|View full text |Cite
|
Sign up to set email alerts
|

Competition between reverse water gas shift reaction and methanol synthesis from CO2: influence of copper particle size

Abstract: Converting CO2 into value-added chemicals and fuels, such as methanol, is a promising approach to limit the environmental impact of human activities. Conventional methanol synthesis catalysts have shown limited efficiency...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 82 publications
(148 reference statements)
2
13
0
Order By: Relevance
“…Qualitatively, the H 13 COO signal (i.e., ν s (CH) 2835 cm −1 ) accurately follows the trend exhibited by 13 CH 3 OH (g) , consistent with this species being the key reaction intermediate, in direct relation to the evidence discussed above (Figure 8b). The comparison between both measurements (i.e., DRIFTS and MS) is possible since (i) the delay in the m/z signal with respect to the registered FTIR bands from formates was estimated to be ∼1 s, far lower than the time scale of the complete experiment (i.e., ∼3600 s) and (ii) the conversion under SSITKA conditions (i.e., ∼0.25%) is lower enough to assume that the coverage of formates is the same all along the DRIFTS cell.…”
Section: R-wgsr + Co Hydrogenation Mechanismsupporting
confidence: 82%
See 1 more Smart Citation
“…Qualitatively, the H 13 COO signal (i.e., ν s (CH) 2835 cm −1 ) accurately follows the trend exhibited by 13 CH 3 OH (g) , consistent with this species being the key reaction intermediate, in direct relation to the evidence discussed above (Figure 8b). The comparison between both measurements (i.e., DRIFTS and MS) is possible since (i) the delay in the m/z signal with respect to the registered FTIR bands from formates was estimated to be ∼1 s, far lower than the time scale of the complete experiment (i.e., ∼3600 s) and (ii) the conversion under SSITKA conditions (i.e., ∼0.25%) is lower enough to assume that the coverage of formates is the same all along the DRIFTS cell.…”
Section: R-wgsr + Co Hydrogenation Mechanismsupporting
confidence: 82%
“…After the isotopic shift, the m/z 33 signal allowed to follow the 13 CH 3 OH formation/consumption. Additionally, the m/z signals 28, 29, 44, and 45 were employed for the monitoring of 12 CO, 13 CO, 12 CO 2 , and 13 CO 2 , respectively. From the results, the residence time of intermediates that lead to a certain product P can be estimated from eq 2.2, recently reported in the literature 29…”
Section: Kinetic Measurements Atmentioning
confidence: 99%
“…2a) and the DFT calculations revealed that the formation of H 2 COO* from HCOO* species is the rate-determining step (RDS) for methanol production over silica-loaded Cu/Mo 2 CT x catalysts. Barberis et al 31 formulated the size effect on Cu/C catalysts in terms of the configuration of surface Cu atoms induced by size change. DFT calculations showed that formate has a greater coverage at the corner and edge sites of Cu as compared to terrace sites and that small-size Cu possesses a surface dominated by the corner and edge sites (Fig.…”
Section: Size-dependent Co2 Hydrogenation Performance In Different Me...mentioning
confidence: 99%
“…[25][26][27] Besides, the changes in the configuration of the surface atoms are inevitably brought about by changes in metal size; in general, small-sized NPs have a greater proportion of corner and edge sites, and these coordination-unsaturated metal atoms are thought to be active for CO 2 hydrogenation. [28][29][30][31] However, for the Cu/ZnO catalyst, it was observed that large Cu NPs (200 nm) exhibited greater intrinsic activity and CH 4 selectivity than other catalysts with smaller Cu size. 32 Although many comprehensive studies have been devoted to investigating the size effect in CO 2 hydrogenation in the past few years, 19,33,34 a unified theory on size-dependent CO 2 hydrogenation performance has not yet been revealed, as the synthesis of metal-loaded catalysts with well-controlled sizes is challenging both conceptually and practically, especially when the size of metal is scaled down to ultra-small clusters or even singleatom (SA) scales.…”
Section: Introductionmentioning
confidence: 98%
“…The methanol economy concept proposed by George A. Olah suggests using methanol as an energy storage material and fuel . Moreover, CH 3 OH is a versatile platform chemical that can not only produce basic chemicals such as formaldehyde but also be converted into hydrocarbons through methanol to olefins or methanol to gasoline processes . Therefore, combining hydrogen from renewable resources with CO 2 to synthesize methanol has garnered significant attention.…”
Section: Introductionmentioning
confidence: 99%